Research on College Students' Mobile Reading Behavior under the Framework of Information Behavior：Taking the Superstar Mobile Reading APP Platform as an Example - Zhao Wenjun; Sun Jinyu (Zhishi guanli luntan, 2020)
［Purpose /significance］Taking the Superstar mobile reading APP as the research platform, this paper explores the behavioral rules of mobile reading for college students. So that, we can provide references and advice for mobile reading service providers to improve service quality.[ Method /process］Taking undergraduates as the research object , this paper adopted the method of questionnaire survey and in-depth interview to obtain the research data, used Excel, SPSS and other statistical tools for statistical analysis of the survey data.［Result /conclusion］At present, the mobile reading service provided by university libraries has such problems as low utilization rate, difficulty in meeting users' demands for resource content, and improvement in interactive experience. Then, the paper proposes some targeted strategies for improving the quality of mobile reading based on the conclusion of the investigation analysis．